Influence lactation stage on milk quality of small holders Etawah crossbreed goats farmer's: Pengaruh periode laktasi terhadap kualitas susu kambing peranakan etawah pada peternakan skala rakyat - Ahmad Khoirul Umam; Lilik Eka Radiati; Naftali Putu Aryudya; Rizky Ramadhan (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2023)
This study aims to determine the effect of the lactation stage on the milk quality of Etawah Peranakan Goats based on pH value, water content, and total microbes in Muda Bakti Barokah Farm. Material used in this research was PE goat fresh milk from 3 different lactation stage i.e. early, mid, and late lactation stages. Completely Randomized Design (CRD) method used in this research, single factor (3 levels of lactation stage) in 15 replication. The research method used a Completely Randomized Design with three treatments and three replications. The data obtained (pH, moisture content, and total microbes) were analyzed by analysis of variance (ANOVA). If there is a significant difference, it is continued with Duncan's Multiple Range Test. The results showed that the lactation stage significantly affected the pH value and moisture content of Etawah crossbreed goat's milk. The total milk microbes of Etawah Peranakan goats during early lactation, mid-lactation, and late lactation ranged from 4.87 – 6.72 CFU/ml. This research concludes that there is a significant effect between early, mid-lactation, and late lactation according to pH values and moisture content. However, it does not affect the total milk microbes of Etawah crossbreed goats